Hollowing Out the Middle? Remittances and Income Inequality in Nigeria - James T. Bang; Aniruddha Mitra; Phanindra V. Wunnava (Institute of Labor Economics (IZA), 2018)
This paper investigates the impact of remittances on poverty and inequality in Nigeria. In contrast to the existing literature, our methodology of instrumental variable quantile regression (IVQR) explicitly demonstrates the differential marginal impact of remittances for households at different levels of the conditional expenditure distribution. Furthermore, in tracing this heterogeneous impact, we are able to address the effect of remittances on poverty and inequality simultaneously in a unified econometric model. Our results reveal a positive marginal impact of remittances at all but the very highest quantiles of the conditional distribution of household expenditure, with the impact being the greatest up to the 12th quantile. While this unambiguously supports the poverty alleviation role of remittances hypothesized in the literature, the distributional impact is more nuanced: The marginal effect of remittance is seen to follow an approximate U-shape over the household expenditure distribution until the 89th quantile, whereupon it drops sharply. As such, households lying between the 13th to the 35th quantile gain far less from receiving remittances than households outside of this range.
Keywords: F22; F24; O15; O55; 330; poverty; income inequality; migration; remittances; instrumental variable; quantile regression